Mechanism of Action of Vitamin K: Evidence for the Conversion of a Precursor Protein to Prothrombin in the Rat - Shah, D. V. (1971)
Previous studies have shown that the vitamin K-induced synthesis of prothrombin in a vitamin K-deficient rat is only slightly inhibited by cycloheximide treatment. Rat prothrombin has now been purified by disc electrophoresis after BaSO(4) adsorption and citrate elution. When cycloheximide (5 mg/kg) was given to vitamin K-deficient rats 30 min before vitamin K, about 70% of the amount of prothrombin seen in rats not treated with cycloheximide was produced (two-stage assay), and the prothrombin band could be seen on the electrophoretic gels. However, if radioactive amino acids are administered to the rats after cycloheximide treatment, the newly formed prothrombin contains no radioactivity. The isolated prothrombin does contain radioactivity if the vitamin K-deficient rats are treated with vitamin K but no cycloheximide. When radioactive amino acids were given to deficient rats 1 hr before cycloheximide and vitamin K, radioactivity was found in prothrombin. These data suggest that, in the intact rat, the action of vitamin K is to convert a protein precursor with a short biological half life to prothrombin.